2005
DOI: 10.1038/nrm1784
|View full text |Cite
|
Sign up to set email alerts
|

How proteins produce cellular membrane curvature

Abstract: Biological membranes exhibit various function-related shapes, and the mechanism by which these shapes are created is largely unclear. Here, we classify possible curvature-generating mechanisms that are provided by lipids that constitute the membrane bilayer and by proteins that interact with, or are embedded in, the membrane. We describe membrane elastic properties in order to formulate the structural and energetic requirements of proteins and lipids that would enable them to work together to generate the memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
1,107
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,196 publications
(1,140 citation statements)
references
References 90 publications
30
1,107
2
1
Order By: Relevance
“…However, a complete dewetting of phase O over phase W1 (from Figure 1a2 to Figure 1a3) also requires 1 < 0, i.e., 2 − ( 1 + 1 2 ) < 0 (2) and 2 > 0, i.e., 1 − ( 2 + 1 2 ) > 0 (3). From equation (1), (2) and (3), we conclude the criterion for complete dewetting of W1/O/W2 emulsion drops is the equation (3). Only if 2 > 0, will the dewetting process go to completion, resulting in separated aqueous (W1) and oil (O) droplets.…”
mentioning
confidence: 87%
“…However, a complete dewetting of phase O over phase W1 (from Figure 1a2 to Figure 1a3) also requires 1 < 0, i.e., 2 − ( 1 + 1 2 ) < 0 (2) and 2 > 0, i.e., 1 − ( 2 + 1 2 ) > 0 (3). From equation (1), (2) and (3), we conclude the criterion for complete dewetting of W1/O/W2 emulsion drops is the equation (3). Only if 2 > 0, will the dewetting process go to completion, resulting in separated aqueous (W1) and oil (O) droplets.…”
mentioning
confidence: 87%
“…Thus, LysoPL levels have to be tightly controlled to maintain cell survival and function. Due to their inverted cone shape LysoPLs influence membrane curvature and, consequently, also the formation and fission of vesicles (36,37). It was shown that increasing the ratio of LysoPL/PL in the outer leaflet of a membrane causes an outward curvature that at its most extreme leads to tubule formation (37).…”
Section: Discussionmentioning
confidence: 99%
“…They assemble to form flat membranes. Conversely, dioleoylphosphatidylethanolamine (DOPE) lipids have a head group smaller than their tail region, giving them negative intrinsic curvature [73].…”
Section: Induced Membrane Deformationmentioning
confidence: 99%